Nietzsche in Hollywood : images of the Übermensch in early American cinema - Rukgaber, Matthew (Albany : State University of New York Press, 2022)
"Argues that Nietzsche's idea of the Übermensch was a central concern of filmmakers in the 1920s and 1930s"--
Introduction: Approaching film with Nietzsche -- 1. The inhuman in the human : social Darwinism and the Übermensch in the silent era -- 2. The weakness in strength : the Übermensch as degenerate in the films of Erich von Stroheim -- 3. The criminal law : the will-to-power and the gangster as Übermensch -- 4. The salvation of sin : conquering sex and the Übermensch as Superwoman -- 5. The truth of lies : the Übermensch as genius in the comedies of Ben Hecht -- 6. The freedom in fate : the Übermensch as Dionysius in the films of Josef von Sternberg -- 7. The revealing mask : the Übermensch as free spirit in the comedies of Ernst Lubitsch -- Conclusion: A Nietzschean philosophy of film.
Includes bibliographical references and index.
Online resource title from digital title page; (viewed on September 13, 2022).
JSTOR
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Influence; Nietzsche, Friedrich Wilhelm, -- 1844-1900; Superman (Philosophical concept); Philosophy in motion pictures; Motion pictures -- United States -- History -- 20th century; Surhomme; Philosophie au cinéma.; Cinéma -- États-Unis -- Histoire -- 20e siècle.; PERFORMING ARTS / Film & Video / History & Criticism; Influence (Literary, artistic, etc.); Motion pictures; Philosophy in motion pictures; Superman (Philosophical concept); United States; 1900-1999; History